Peningkatan Keaktifan Siswa Melalui Tutor Sebaya Kegiatan P5 Project Demokrasi di SMPN 41 Surabaya - Ninik Ninik (Jurnal Didaktika Pendidikan Dasar, 2022)
Implementation of the Pancasila Student Profile Strengthening Project (P5) at SMPN 41 Surabaya for the theme of democracy was integrated into several subjects, namely PKN, Indonesian, Cultural Arts and Javanese in the Merdeka Curriculum. The heterogeneity of students' intelligence in completing group assignments encourages teachers to carry out classroom actions using the peer tutor model. This class action was carried out in two cycles with the same stages, namely planning, implementing, observing and reflecting. There was an increase in student learning outcomes from cycle I to cycle I. In cycle I, 27 students entered the upper category and in cycle 2 all students (30 people) entered the upper category.